Improvement of the Conductive Ability of Polymer Electrolytes - Xu Hailiang (E3S Web of Conferences)
In current applied research, traditional electrolytes face significant challenges. The emergence and application of polymer electrolytes provide effective solutions to these problems. This paper will introduce the types and characteristics of polymer electrolytes based on three aspects. The star-shaped compound based on PEGMA, i.e., poly(ethylene glycol) methacrylate, can significantly enhance the mechanical and electrical properties of polymer electrolytes; the gel electrolyte prepared by compounding highly polar β-polyvinylidene fluoride (β-PVDF) with nylon 6 shows significant application potential in improving ion conduction efficiency and enhancing battery safety. Brush-shaped polymers have good performance in avoiding the crystallization of linear polymers and inhibiting the growth of lithium dendrites and improving mechanical strength. These three types of polymer electrolytes each have their characteristics and good application prospects. Still, they all face problems such as high cost and difficulties in industrialization at the present stage and need further development to better benefit human society. This paper aims to provide those who want to explore and do some decent research on this topic with some basic information as well as fundamental advice.